Borrowing Constraints, Household Debt, and Racial Discrimination in Loan Markets - Duca, John V.; Rosenthal, Stuart S. (Journal of Financial Intermediation, 1993)
Two-step selection methods are applied to the 1983 Survey of Consumer Finances to examine the extent to which borrowing constraints restrict household access to debt and the manner in which lenders vary debt limits across borrowers. Results indicate that 30% of young families are credit constrained, and that roughly half of these families would hold at least $12,000 (1982 dollars) more debt if borrowing constraints were relaxed. Debt limits increase with income and wealth, and are relaxed for families with a good credit history. In addition, minorities face tighter debt limits and are more likely to be credit constrained than white families. Journal of Economic Literature Classification Numbers: E51, J71, D12.